Evolusi Busana dari Era Islam Klasik hingga Abad Pertengahan - Kholilurrahman, M. (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
This study explores the evolution of fashion from the classical Islamic era to the medieval period, highlighting the changes in styles, materials, and cultural influences that shaped clothing across various regions in the Islamic world. Starting with the principles of simplicity and modesty advocated in Islamic teachings, early clothing was more functional and reflected religious values. As the caliphate expanded and interacted with other civilizations, such as Persia, Byzantium, and Europe, clothing became more diverse and rich in adornment, with the use of luxurious materials like silk and brocade. This study also examines how trade, cultural exchanges, and social changes contributed to the transformation of clothing, creating a unique blend of local traditions and foreign influences. Additionally, the research discusses how clothing served not only as a means of covering the body but also as a symbol of social status, cultural identity, and artistic expression. Through historical and textual analysis, this study aims to provide a comprehensive understanding of the development of fashion in the context of Islamic history and its impact on modern fashion.